2015
DOI: 10.4161/auto.36098
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the ubiquitin-binding domain of OPTN/optineurin interfere with autophagy-mediated degradation of misfolded proteins by a dominant-negative mechanism

Abstract: OPTN (optineurin) is an autophagy receptor and mutations in the OPTN gene result in familial glaucoma (E50K) and amyotrophic lateral sclerosis (ALS) (E478G). However, the mechanisms through which mutant OPTN leads to human diseases remain to be characterized. Here, we demonstrated that OPTN colocalized with inclusion bodies (IBs) formed by mutant HTT/huntingtin protein (mHTT) in R6/2 transgenic mice and IBs formed by 81QNmHTT (nuclear form), 109QmHTT (cytoplasmic form) or the truncated form of TARDBP/TDP-43 (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
102
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(109 citation statements)
references
References 53 publications
(80 reference statements)
3
102
0
Order By: Relevance
“…Previous work has suggested a direct interaction mediated by the RRL motif in myosin VI and the UBDs of optineurin (Sahlender et al, 2005; Shen et al, 2015). Our results suggest that ubiquitin may be part of the myosin VI interaction with this adaptor protein.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has suggested a direct interaction mediated by the RRL motif in myosin VI and the UBDs of optineurin (Sahlender et al, 2005; Shen et al, 2015). Our results suggest that ubiquitin may be part of the myosin VI interaction with this adaptor protein.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies of the effects of OPTN mutations have suggested a dominant‐negative or gain‐of‐function effect for many of the characterized disease‐associated variants (Shen et al. 2014; Turturro et al. 2014).…”
Section: Discussionmentioning
confidence: 99%
“…With the discovery of p62 as a selective autophagy receptor, it became clear that selective autophagy of protein aggregates may play an important role in neurodegenerative diseases[83]. Given the importance of this degradation pathway, it is not surprising that there is a significant amount of redundancy with multiple selective autophagy receptors also mediating aggrephagy including NBR1 and OPTN[54,71]. …”
Section: P62: Multi-functional Selective Autophagy Receptor With Rolementioning
confidence: 99%